Andrea Furst on change and uncertainty (Supporting champions, 2020)
In this episode I talk to Dr Andrea Furst, performance psychologist at Mental Notes. Andrea has had a highly successful career supporting some of the highest performing teams to the highest performances. She has worked in Australia, where she originates from, Singapore and now based in the UK. She has supported the Australian kayak team, Singapore sailing, GB Hockey and is widely sought after in professional sports and supporting business leaders. Andrea brings a really grounded, pragmatic approach to her practice. She is thoughtful and intuitive, but shrewd and no nonsense. In this conversation we discuss some of the emotions and challenges everyday people and athletes will be experiencing during this lockdown period, what methods and ways of thinking can help people cope and thrive. What I really enjoyed about this conversation was not only hearing about the mental models and ideas that help people cope with change, but I was compelled by her approach of putting the human needs first on the path toward self-discovery. So let`s jump straight into the conversation.